Constraining the stellar energetic particle flux in young solar-like stars. Issue Volume 14:Issue S345(2019) (August 2018) - Rab, Ch.; Padovani, M.; Güdel, M.; Kamp, I.; Thi, W-F.; Woitke, P.
Abstract: Anomalies in the abundance measurements of short lived radionuclides in meteorites indicate that the protosolar nebulae was irradiated by a large number of energetic particles (E≳ 10 MeV), often called solar cosmic rays. The particle flux of the contemporary Sun cannot explain these anomalies, but, similar to T Tauri stars, the young Sun was more active and probably produced enough high energy particles. However, the stellar particle (SP) flux of young stars is essentially unknown. We model the impact of high-energy ionization sources on the chemistry of the circumstellar environment (disks and envelopes). The model includes X-ray radiative transfer and makes use of particle transport models to calculate the individual molecular hydrogen ionization rates. We study the impact on the chemistry via the ionization tracers HCO + and N2 H + . We argue that spatially resolved observations of those molecules combined with detailed models allow for disentangling the contribution of the individual high-energy ionization sources and to put constraints on the SP flux in young stars.